Is Climate Transition Risk Priced into Corporate Credit Risk? Evidence from Credit Default Swaps - Andrea Ugolini; Juan C. Reboredo; Javier Ojea-Ferreiro (Fondazione Eni Enrico Mattei (FEEM), 2023)
We study whether climate transition risk is reflected in the credit default swap (CDS) spreads of firms. Using information on the vulnerability of a firm's value to the transition to a low carbon economy, we construct a climate transition risk (CTR) factor, and document how this factor shifts the term structure of the CDS spreads of more vulnerable firms but not of less vulnerable firms. Considering the impact of different climate transition policies on the CTR factor, we find that they have asymmetric and significant economic impacts on the credit risk of more vulnerable firms, and negligible effects on the remaining firms.
Keywords: C24; G12; G32; Q54; 330; Climate transition risk; CDS spreads; credit risk